Hydrogels: Skin‐Inspired Multifunctional Autonomic‐Intrinsic Conductive Self‐Healing Hydrogels with Pressure Sensitivity, Stretchability, and 3D Printability (Adv. Mater. 31/2017). Issue 31 (August 2017) - Darabi, Mohammad Ali; Khosrozadeh, Ali; Mbeleck, Rene; Liu, Yuqing; Chang, Qiang; Jiang, Junzi; Cai, Jun; Wang, Quan; Luo, Gaoxing; Xing, Malcolm
Abstract : A double network chitosan‐based hydrogel with bulk conductivity, mechanical and electrical self‐healing properties, ultra‐stretchability and pressure sensitivity in chemical and physical crosslinking networks, together with ionic conductivity and polypyrrole networks is presented in article number1700533 by Gaoxing Luo, Malcolm Xing, and co‐workers. Wirelessly connected via smart phone, this stretchable 3D‐printed sensor can monitor pulse and muscle motions.